The Influence Of Celebrity Endorser and Brand Image on Purchase Decisions for Somethinc Skincare Products on the Online Shop Platform - Dhia, Muhammad Rafi; Melinda, Shelsa (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
This study aims to explore the influence of brand perception and celebrity endorsements on consumers' decisions to purchase Somethinc skincare products through online marketplaces. The purchase decision serves as the dependent variable, while celebrity endorsers and brand image are the independent variables. Using a quantitative, associative approach, primary data was collected from respondents in South Tangerang who have purchased and used Somethinc skincare products. Random sampling was applied, and SPSS was used for data analysis. The findings reveal that celebrity endorsers have a significant positive effect on purchase decisions, and brand image also plays a substantial role in influencing these decisions. The overall results indicate that both celebrity endorsers and brand image significantly impact purchase decisions.